Management and Outcome of Rare Cases of Bilateral Symmetrical Radial Head Fracture - Virender Kumar; Rajesh Rohilla; Ipanshu Malik; Paul Therattil; Gopal Bedia; Sonu Kumar (Journal of Orthopaedic Diseases and Traumatology)
Background: Isolated radial head fractures are uncommon, accounting for just 1%–2% of all elbow fractures. Bilateral radial head fractures are much more unusual, with only a few occurrences documented. The most common elbow fractures are radial head and neck fractures. A fall onto an extended hand with a partially flexed elbow is the most common cause of this injury. Aims and Objectives: To assess the efficiency of conservative management of bilateral Mason Type I and II Radial Head Fractures. Materials and Methods: Nine patients with bilateral Mason type I and II radial head fractures were included in the study. All were treated using conservative management and physiotherapy. Primary evaluation of the patients was conducted regarding the presence of other injuries and associated complications. After the confirmation of the diagnosis, patients are advised immobilization for the first few days along with ice fomentation. Patients with moderate swelling are advised an above elbow posterior slab for a few days. The rehabilitation oh the patients were done in three phases. Assessment of final outcome, both radiological and functional, was done at the end of 6 months. Results: At the 6 month follow up, the patients were asymptomatic and had a complete range of motion at the elbow joints, including supination and pronation. The patients had no additional symptoms. As expected, type I radial head fractures responded better and quicker to physiotherapy than type II fractures. Each and every patient was successfully managed at the end of 6 months with no complications or residual symptoms. Conclusion: Patients after a trauma to the elbow are likely to ignore the fracture as there is a near complete range of motion in flexion and extension. Pain, swelling, and localized soreness across the lateral side of the elbow are all symptoms of a radial head fracture. The advantage of early diagnosis of radial head fracture is that it can be managed and treated successfully with proper rehabilitation for a few months. The patient and the attending doctor can observe the gradual relief of symptoms and steady improvement in movements of the elbow. Hence, it is proved that conservative management is the gold standard treatment for Type I and II Mason radial head fractures as it re establishes the complete function of the elbow and forearm and significantly improves the quality of life.